A Building Information Management (BIM) Framework and Supporting Case Study for Existing Building Operations, Maintenance and Sustainability. (2015) - McArthur, J.J.
Abstract: Building Information Management (BIM) models are transforming how buildings are designed and constructed, and can facilitate multi-disciplinary coordination, and integrate 3D design, analysis, cost estimating, and construction scheduling. By extending the model into the post-occupancy period, BIM models can be used to support Facilities Management and Building Operations, and offer a consolidated interface for information regarding all aspects of building operational performance. Four key challenges must be overcome to develop BIM models suitable for Sustainable Operations management: (1) identification of critical information required to inform Operational decisions, (3) the high level of effort to create new or modify existing BIM models for the building(s), (2) the management of information transfer between real-time operations and monitoring systems and the BIM model, and (4) the handling of uncertainty based on incomplete building documentation. This paper describes the process used to addresses and overcome each of these challenges. The BIM framework and its refinement are presented along with evaluative data from a case study where a model was developed using this framework for a complex university building. The results of this study demonstrate how these BIM models can be developed for the most challenging existing building scenarios and effectively used to improve building management and performance.